Bacha bazi in Afghanistan: A study of intersectional feminism - Golijot, Jonathan Willem; Bimantoro, Aditya Sukma; Rizqia, Sabila Arfa; Nuraeni, Nuraeni (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
This article aimed to understand of the practice of bacha bazi, a widespread sexual exploitation and abuse of boys in Afghanistan in the guise of performances in which boys dance as women. Guided by intersectional feminist theory, the research examined the intersecting patriarchal discourses of class, gender, power inequality that support this exploitation. The study employed humane research methods, such as document analysis, to gather and analyze data thematically from the sources studied. The study showed how vulnerable boys are exploited by powerful adult men and forced into bacha bazi in exchange for money or protection. The study attested to bacha bazi having its roots in patriarchal Afghan society where gender roles and power dynamics are rigid and boys are disenfranchised and their victimization normalized. The study cited economic despair and social inequality as inducing families to sell their sons to exploitation. The research, through intersectional feminist analysis, reveals the complex intersection of gender, power, and class that informs the practice. The research facilitated in theorizing about structural inequalities to facilitate sexual exploitation and justice and equality for all marginalized peoples in Afghanistan. The study saw that the issue requires a range of solutions from legal reform to economic assistance, through cultural change, in addressing the causes of bacha bazi and protecting vulnerable children.